'In Quest of Narrative': A Teacher's Furore and Textual Returns. Issue 3 (2nd July 2016) - Yoder, Amarou
Abstract: This paper explores a teacher's furore− my own − by asking how such furores might be considered 'in quest of narrative'. If so, which one? The answer, I suggest, lies in revisiting the source texts for such a furore, allowing the texts to illuminate the curricula and teaching, rather than the reverse. In so doing, the ethical claim of the texts in which such a furore originates might be recovered, in order to clarify one's implication in webs of violence. Interspersed with an exploration of Katabatic narratives and curricula − the vehicle for my furore to teach about violence − are three narrative vignettes that emerged from revisiting the texts that inspired my teaching.